2022
DOI: 10.1371/journal.pone.0266395
|View full text |Cite
|
Sign up to set email alerts
|

Tracing back variations in archaeal ESCRT-based cell division to protein domain architectures

Abstract: The Endosomal Sorting Complex Required for Transport (ESCRT) system is a multi-protein machinery that is involved in cell division of both Eukaryotes and Archaea. This spread across domains of life suggests that a precursor ESCRT machinery existed already at an evolutionary early stage of life, making it a promising candidate for the (re)construction of a minimal cell division machinery. There are, however, only few experimental data about ESCRT machineries in Archaea, due to high technical challenges in culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Recent examination of CdvB protein sequences suggested that most of them harbor a C-terminal MIT interaction motif 2 (MIM2) that is conserved in Vps20/32/60 subunit class (53) (Figure 2). Most of the TACK genomes encode additional ESCRT III family proteins that, however, lack the wH extension as noticed previously (54). Furthermore, in thaumarchaea, none of the CdvB family proteins contain fused wH domains (54).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Recent examination of CdvB protein sequences suggested that most of them harbor a C-terminal MIT interaction motif 2 (MIM2) that is conserved in Vps20/32/60 subunit class (53) (Figure 2). Most of the TACK genomes encode additional ESCRT III family proteins that, however, lack the wH extension as noticed previously (54). Furthermore, in thaumarchaea, none of the CdvB family proteins contain fused wH domains (54).…”
Section: Resultsmentioning
confidence: 60%
“…Domain boundaries for Saccharomyces cerevisiae are based on previously published structures and analyses (19, 55, 98). For archaeal proteins, domain boundaries are based either on previous analyses (22, 35, 53, 54) or on sequence analysis performed during this work as described under Methods. S. cerevisiae gene names are highlighted in red on the right.…”
Section: Introductionmentioning
confidence: 99%
“…ESCRT-mediated membrane remodeling is a conserved phenomenon in the cytoplasm of all eukaryotic cells. However, the recent biochemical characterization of eukaryotic-like ESCRT-I, ESCRT-II, and ESCRT-III components in Asgard archaea suggests a pre-eukaryotic origin for the ESCRT machinery (42)(43)(44). In line with this hypothesis, recent structural analyses have highlighted PspA, a bacterial protein important for membrane integrity, and VIPP1, a critical protein for thylakoid biogenesis in cyanobacteria and chloroplasts of photosynthetic eukaryotes, as members of the ESCRT-III family of proteins, capable of inducing membrane deformation upon binding (18,19,21).…”
Section: Discussion-mentioning
confidence: 99%
“…While all other archaea encode only for homologs of the ESCRT-III/VPS4 module, Asgard archaea encode for homologs of the complete ESCRT system (ESCRT-I-III and VPS4) (6,7). Additionally, the sequence of Asgard ESCRT-III/VPS4 proteins is more closely related to those of eukaryotes than to other archaeal ESCRT systems (the CDV system) (5,20). Lastly, VPS4 homologs of Asgard archaea were shown to functionally interact with eukaryotic ESCRTs in both yeast and mammalian cells (5,26).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced, simplified ESCRT-III systems have been identified in prokaryotes including in bacteria and archaea (named Vipp1 and PspA in bacteria and CdvB in archaea) (7, 20, 21). While the bacterial homologs were shown to remodel membranes in vitro, no VPS4 was identified in this system so far, and whether these distant homologs can sever membranes has not been clarified.…”
Section: Introductionmentioning
confidence: 99%